PENDIDIKAN ANAK DIFABEL DI SURAKARTA 1950an-1970an - , RIZKA INTAFANI; , Nur Aini Setiawati, M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Disability educations beginning with the rehabilitation places are concentrated in Surakarta like Dr. Soeharso Rehabilitation Centrum. The establishment of society foundations is given attention the lives of the disabled in Surakarta, appeared issues raised are intended for education about disabilities in the year 1950 where it was legalized early years education rights of children and adults with disabilities by American. By using the method of writing the history taken by unique idea, collecting resource, verification datum and interpretation, and writing method. This paper is expected to provide more information for the reader about the education which is aimed for disabled people in the 1950s, especially in Surakarta. The continued development of role of the government and society, was established foundations dedicated to people with disabilities such as Yayasan Pemelihara Anak Cacat (YPAC) and other foundations that are established to serve the disabled. Foundations also provide education for disabled children of school age to be able to live more independently, and able to reach their full potential. Therefore, the government began to inaugurate schools are reserved for disabled people, or commonly called Sekolah Luar Biasa (SLB).